Independent examination of the records of the Sydney Olympics 2000 Bid Ltd. - Sheridan, T. A.
The primary focus of my Examination, under its Terms of Reference, was to determine the level of compliance with the IOC guidelines by the Bid Company and its officers during the bid period. However, the Examination's findings, which are summarised below, must be viewed in the context of the environment during the bid period and the level of monitoring which the IOC itself applied to the guidelines. In the context of the environment it is important to understand that: